Electromagnetic wave shield sheet
Patent Information
- Application Number
- JP2023148440
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-13
- Publication Date
- 2025-03-26
AI Technical Summary
【0008】 本発明の電磁波シールドシートは、所定の層構成とすることにより、非常に薄いシートとした場合であっても電磁波シールド性に優れている。
Smart Images

Figure 2025041254000001 
Figure 2025041254000002
Abstract
Description
[Technical field]
[0001] The present invention relates to an electromagnetic wave shielding sheet. [Background technology]
[0002] Electromagnetic waves generated from various devices such as printed wiring boards, electronic components, and antennas interfere with each other, and may affect other electric circuits and electronic components, causing malfunctions, etc. Therefore, there is a demand for preventing malfunctions of various devices by using electromagnetic wave shielding sheets to improve the electromagnetic shielding properties of the various devices.
[0003] As an electromagnetic wave shielding sheet, for example, Patent Document 1 discloses a multilayer material for shielding low-frequency electromagnetic waves, the multilayer material including a plurality of repeating material alternating layer sets, each of which includes a conductive layer and a magnetic layer. Patent Document 2 discloses a non-flammable electromagnetic wave shielding laminate including an aluminum foil layer, an adhesive layer, and a base layer, the aluminum foil layer being the outermost layer on one or both sides of the non-flammable electromagnetic wave shielding laminate, the adhesive layer being a layer that bonds the aluminum foil layer, and the base layer including a spunbond layer. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2022-75645 [Patent Document 2] JP 2019-179786 A Summary of the Invention [Problem to be solved by the invention]
[0005] However, Patent Document 1 states that it is specialized in shielding electromagnetic waves having frequencies less than about 1 MHz, and Figures 2 to 4, which are given as specific examples of multilayer materials, disclose only multilayer materials having multiple sets of alternating conductive and magnetic layers, and there is a problem that such a laminate structure has insufficient electromagnetic shielding properties at frequencies of about 10 to 100 MHz. Also, although Patent Document 2 is an invention related to an electromagnetic shielding laminate, it aims to increase heat resistance by including a spunbond layer, and there is room for improvement in electromagnetic shielding properties.
[0006] An object of the present invention is to provide an electromagnetic wave shielding sheet having excellent electromagnetic wave shielding properties. [Means for solving the problem]
[0007] That is, the present invention includes the following inventions. [1] An electromagnetic wave shielding sheet comprising a first conductive layer, a second conductive layer, and a magnetic layer, wherein one main surface of the electromagnetic wave shielding sheet is the first conductive layer, the other main surface is the second conductive layer, the magnetic layer is between the first conductive layer and the second conductive layer, the first conductive layer and the second conductive layer both contain a conductive material, and the magnetic layer contains a magnetic material. [2] The electromagnetic wave shielding sheet according to [1], wherein the conductive material includes at least one selected from the group consisting of conductive polymers, metals, metal oxides, and carbon-based materials. [3] The electromagnetic wave shielding sheet according to [1] or [2], wherein the magnetic material is a soft magnetic material. [4] The electromagnetic shielding sheet according to any one of [1] to [3] above, further comprising a nonwoven fabric layer as an intermediate layer. [5] The electromagnetic shielding sheet according to [4], wherein the nonwoven fabric layer contains a polyester resin. [6] An electromagnetic wave shielding sheet according to any one of [1] to [5] above, having a thickness of 900 μm or less, a magnetic field shielding property at 100 MHz measured by the KEC method of 80 dB or more, and an electric field shielding property at 10 MHz of 60 dB or more. Effect of the Invention
[0008] The electromagnetic wave shielding sheet of the present invention has a predetermined layer structure, and therefore has excellent electromagnetic wave shielding properties even when made into a very thin sheet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0009] The electromagnetic shielding sheet of the present invention comprises a first conductive layer, a second conductive layer, and a magnetic layer, one main surface of which is the first conductive layer, the other main surface of which is the second conductive layer, and the magnetic layer is between the first conductive layer and the second conductive layer. Note that the main surface refers to the surface perpendicular to the lamination direction (thickness direction) of the electromagnetic shielding sheet.
[0010] <Conductive layer> Both the first conductive layer and the second conductive layer contain a conductive material. The electromagnetic shielding sheet of the present invention preferably contains a conductive layer in addition to the first conductive layer and the second conductive layer (contains a conductive layer as an intermediate layer). When a conductive layer is included in addition to the first conductive layer and the second conductive layer, all of the conductive layers provided in the electromagnetic shielding sheet of the present invention contain a conductive material.
[0011] The conductive material is not particularly limited, but preferably includes at least one selected from the group consisting of conductive polymers, metals, metal oxides, and carbon-based materials, and more preferably includes a metal. The conductive material may be one type or two or more types.
[0012] Examples of conductive polymers include polyacetylene, polypyrrole, poly(3,4-ethylenedioxythiophene), poly(3,4-ethylenedioxythiophene) / polystyrenesulfonate, polythiophene, polyaniline, poly(p-phenylene), polyfluorene, polycarbazole, and polysilane.
[0013] Examples of metals include elemental metals such as gold, silver, copper, and aluminum; and alloys containing one or more of these elemental metals, with aluminum being preferred.
[0014] Examples of metal oxides include tin-doped indium oxide (ITO), antimony-doped tin oxide (ATO), and fluorine-doped tin oxide (FTO).
[0015] Examples of carbon-based materials include compounds having a carbon skeleton, such as carbon nanotubes, carbon nanofibers, CN nanotubes, CN nanofibers, BCN nanotubes, BCN nanofibers, graphene, carbon microcoils, carbon nanocoils, carbon nanohorns, carbon nanowalls, and carbon black.
[0016] The conductive layer preferably contains 90% by mass or more of conductive material, more preferably 95% by mass or more, even more preferably 98% by mass or more, and particularly preferably 100% by mass (the conductive layer consists only of the conductive material).
[0017] The total thickness of all conductive layers is preferably 200 μm or less, more preferably 150 μm or less, even more preferably 100 μm or less, and particularly preferably 80 μm or less. In the present invention, by making the electromagnetic shielding sheet have a predetermined layer structure, even an electromagnetic shielding sheet with a very thin conductive layer thickness of 200 μm or less has excellent electromagnetic shielding properties. The lower limit of the thickness is not particularly limited, but is, for example, 10 μm or more, and preferably 20 μm or more.
[0018] The total weight of all conductive layers is 20 to 200 g / m 2 It is preferable that the thickness is 30 to 150 g / m 2 More preferably, the thickness is 40 to 100 g / m 2 In the present invention, by forming the electromagnetic wave shielding sheet into a predetermined layer structure, it is more preferable that the conductive layer has a thickness of 200 g / m 2 Even with a basis weight as low as or less, it has excellent electromagnetic wave shielding properties.
[0019] <Magnetic layer> The magnetic layer includes a magnetic material. The magnetic material preferably includes at least one selected from the group consisting of metals and metal oxides, and more preferably is a metal. Examples of the metal include simple metals such as iron, nickel, and cobalt; sendust (Fe-Si-Al alloy), silicon steel (Fe-Si alloy), Fe-Al alloy, permalloy (Fe-Ni alloy), magnetic stainless steel (Fe-Cr-Al-Si alloy), silicon copper (Fe-Cu-Si alloy), Fe-Si-Cr alloy, Fe-Si-Al-Ni alloy, Fe-Ni-Si-Co alloy, Fe-Ni-Si-Co-Cr alloy, Fe-based amorphous alloy, and Fe-based nanocrystalline alloy; and examples of the metal oxide include ferrite represented by AFe2O4 (A is Mn, Co, Ni, Cu, or Zn). Among them, soft magnetic materials such as iron, sendust, Fe-Si alloy, permalloy, magnetic stainless steel, and silicon copper are preferable, and sendust is more preferable.
[0020] The magnetic layer preferably contains a resin in addition to the magnetic material. When the magnetic layer contains a resin, the content of the resin in the magnetic layer relative to 100 parts by mass of the magnetic material is preferably 30 to 200 parts by mass, more preferably 40 to 160 parts by mass, and even more preferably 50 to 120 parts by mass.
[0021] The resin constituting the magnetic layer is preferably a thermoplastic resin, specifically at least one selected from the group consisting of polyester-based resins, polyester urethane-based resins, polyamide-based resins, polyamideimide-based resins, phenoxy-based resins, olefin-based resins, and acrylic-based resins, with polyester-based resins being more preferred.
[0022] The resin constituting the magnetic layer may be a crosslinked thermoplastic resin in which a thermoplastic resin is crosslinked by a crosslinking agent, and is preferably a crosslinked polyester resin in which a polyester resin is crosslinked by a crosslinking agent. The crosslinking agent is not particularly limited and can be appropriately selected depending on the purpose, but examples thereof include isocyanate-based crosslinking agents, melamine-based crosslinking agents, and epoxy-based crosslinking agents, and is preferably an isocyanate-based crosslinking agent. In addition, as the crosslinking agent, commercially available products may be used. For example, as an isocyanate-based crosslinking agent, Millionate (registered trademark) N, Coronate (registered trademark) T, Coronate (registered trademark) HL, Coronate (registered trademark) 2030, Suprasec (registered trademark) 3340, Daltosec 1350, Daltosec 2170, Daltosec 2280 (all manufactured by Nippon Polyurethane Industry Co., Ltd.) and the like can be mentioned. As a melamine-based crosslinking agent, Nikalac (registered trademark) MS-11, Nikalac (registered trademark) MS21 (all manufactured by Sanwa Chemical Co., Ltd.), Super Beckamine (registered trademark) L-105-60, Super Beckamine (registered trademark) J-820-60 (all manufactured by DIC Corporation) and the like can be mentioned. As an epoxy-based crosslinking agent, Hardener HY951, Hardener HY957 (all manufactured by BASF), Sumicure DTA, Sumicure TTA (all manufactured by Sumitomo Chemical Co., Ltd.) and the like can be mentioned. Among these, polyfunctional isocyanate compounds are more preferable, and a commercially available product thereof is Coronate (registered trademark) HL manufactured by Tosoh Corporation, which is a trimer adduct of trimethylolpropane and hexamethylene diisocyanate.
[0023] The thickness of the magnetic layer is preferably 30 to 500 μm, more preferably 50 to 400 μm, further preferably 70 to 350 μm, and particularly preferably 100 to 300 μm. In the present invention, the electromagnetic shielding sheet has a predetermined layer structure, so that even an extremely thin electromagnetic shielding sheet having a magnetic layer thickness of 600 μm or less has excellent electromagnetic shielding properties. The electromagnetic shielding sheet of the present invention has at least one magnetic layer, but may have only one magnetic layer or two or more magnetic layers. When the electromagnetic shielding sheet has multiple magnetic layers, the thickness of the magnetic layer refers to the total thickness of all the magnetic layers provided in the electromagnetic shielding sheet.
[0024] The weight of the magnetic layer is 50 to 700 g / m 2 It is preferable that the thickness is 100 to 500 g / m 2 More preferably, the thickness is 150 to 400 g / m 2 In the present invention, by forming the electromagnetic wave shielding sheet into a predetermined layer structure, the magnetic layer has a thickness of 700 g / m 2 Even with a basis weight as low as or less, the electromagnetic shielding sheet has excellent electromagnetic shielding properties. When multiple magnetic layers are provided in the electromagnetic shielding sheet, the basis weight of the magnetic layers mentioned above refers to the total basis weight of all the magnetic layers provided in the electromagnetic shielding sheet.
[0025] In the electromagnetic wave shielding sheet of the present invention, the basis weight of the magnetic material alone is 30 to 500 g / m 2 It is preferable that the thickness is 50 to 400 g / m 2 More preferably, the thickness is 70 to 300 g / m 2 In the present invention, by forming the electromagnetic wave shielding sheet into a predetermined layer structure, the total weight of the sheet is preferably 500 g / m 2 Even a small amount of magnetic material of less than 1000 μm has excellent electromagnetic shielding properties. When multiple magnetic layers are provided in the electromagnetic shielding sheet, the basis weight of only the magnetic layers mentioned above refers to the total basis weight of only the magnetic material in all the magnetic layers provided in the electromagnetic shielding sheet.
[0026] <Nonwoven fabric layer> The electromagnetic shielding sheet of the present invention may further include a nonwoven fabric layer as an intermediate layer. That is, not only a magnetic layer but also a nonwoven fabric layer may be included between the first conductive layer and the second conductive layer. By including a nonwoven fabric layer, cushioning properties and elasticity in the thickness direction are improved, and installation in uneven or curved areas becomes easier. The electromagnetic shielding sheet of the present invention may include only one nonwoven fabric layer or two or more nonwoven fabric layers.
[0027] The nonwoven fabric constituting the nonwoven fabric layer is not particularly limited, and examples thereof include polyester nonwoven fabric, polypropylene nonwoven fabric, polyamide nonwoven fabric, and polyurethane nonwoven fabric. However, it is preferable that the nonwoven fabric layer contains a polyester resin, and it is more preferable that the nonwoven fabric constituting the nonwoven fabric layer is a polyester nonwoven fabric.
[0028] The nonwoven fabric constituting the nonwoven fabric layer may be one obtained by a known method such as a dry method, a wet method, a spunbond method, a melt-blowing method, a flash spinning method, a thermal bond method, a chemical bond method, a needle punch method, a spunlace method, a steam jet method, etc. In addition, a commercially available product may be used as the nonwoven fabric constituting the nonwoven fabric layer.
[0029] The thickness of the nonwoven fabric layer is preferably 700 μm or less, more preferably 600 μm or less, and even more preferably 500 μm or less. The lower limit of the thickness is not particularly limited, but is, for example, 100 μm or more, and preferably 200 μm or more. In addition, when the electromagnetic wave shielding sheet is provided with multiple nonwoven fabric layers, the thickness of the nonwoven fabric layer mentioned above refers to the total thickness of all the nonwoven fabric layers provided on the electromagnetic wave shielding sheet.
[0030] The weight of the nonwoven layer is 20 to 300 g / m 2 It is preferable that the thickness is 40 to 200 g / m 2 More preferably, the thickness is 60 to 150 g / m 2It is more preferable that the weight per unit area of the nonwoven fabric layer is the total weight per unit area of the nonwoven fabric layer. When the electromagnetic wave shielding sheet has a plurality of nonwoven fabric layers, the weight per unit area of the nonwoven fabric layer refers to the total weight per unit area of the nonwoven fabric layers.
[0031] <Binder layer> In laminating a conductive layer and a magnetic layer, a conductive layer and a nonwoven fabric layer, and a magnetic layer and a nonwoven fabric layer, a binder layer may be interposed between the layers, if necessary.
[0032] The binder layer is formed from a resin composition. The resin constituting the binder layer is preferably a thermoplastic resin, specifically, at least one selected from the group consisting of polyester-based resins, polyester urethane-based resins, polyamide-based resins, polyamideimide-based resins, phenoxy-based resins, olefin-based resins, and acrylic-based resins, and more preferably a polyester-based resin.
[0033] The resin composition for forming the binder layer may contain a crosslinking agent in addition to the resin. The binder layer may contain a crosslinked thermoplastic resin obtained by crosslinking a thermoplastic resin, and preferably contains a crosslinked polyester resin obtained by crosslinking a polyester resin. The crosslinking agent is not particularly limited and can be appropriately selected according to the purpose, and examples thereof include isocyanate-based crosslinking agents, melamine-based crosslinking agents, and epoxy-based crosslinking agents, and is preferably an isocyanate-based crosslinking agent. In addition, as the crosslinking agent, commercially available products may be used. For example, as an isocyanate-based crosslinking agent, Millionate (registered trademark) N, Coronate (registered trademark) T, Coronate (registered trademark) HL, Coronate (registered trademark) 2030, Suprasec (registered trademark) 3340, Daltosec 1350, Daltosec 2170, Daltosec 2280 (all manufactured by Nippon Polyurethane Industry Co., Ltd.) and the like can be mentioned. As a melamine-based crosslinking agent, Nikalac (registered trademark) MS-11, Nikalac (registered trademark) MS21 (all manufactured by Sanwa Chemical Co., Ltd.), Super Beckamine (registered trademark) L-105-60, Super Beckamine (registered trademark) J-820-60 (all manufactured by DIC Corporation) and the like can be mentioned. As an epoxy-based crosslinking agent, Hardener HY951, Hardener HY957 (all manufactured by BASF), Sumicure DTA, Sumicure TTA (all manufactured by Sumitomo Chemical Co., Ltd.) and the like can be mentioned. Among these, polyfunctional isocyanate compounds are more preferable, and a commercially available product thereof is Coronate HL manufactured by Tosoh Corporation, which is a trimer adduct of trimethylolpropane and hexamethylene diisocyanate.
[0034] <Physical properties and layer structure of electromagnetic wave shielding sheet> The electromagnetic shielding sheet of the present invention preferably has a thickness of 900 μm or less, more preferably 800 μm or less, even more preferably 700 μm or less, particularly preferably 600 μm or less, and most preferably 500 μm or less. In the present invention, the electromagnetic shielding sheet has a predetermined layer structure, so that even a very thin electromagnetic shielding sheet having a thickness of 900 μm or less has excellent electromagnetic shielding properties. The lower limit of the thickness is not particularly limited, but is, for example, 50 μm or more, and preferably 100 μm or more.
[0035] The electromagnetic wave shielding sheet of the present invention has a basis weight of 2000 g / m 2 It is preferable that the thickness is less than 1500 g / m 2 More preferably, it is 1000 g / m or less. 2 More preferably, it is 700 g / m or less. 2 It is particularly preferable that the weight is 500 g / m or less. 2 It is most preferable that the weight per unit area is 2000 g / m or less. 2 Even with a basis weight as low as 100 g / m or less, the sheet has excellent electromagnetic shielding properties. 2 More than 200g / m 2 More preferably, it is equal to or greater than this.
[0036] The electromagnetic wave shielding sheet of the present invention preferably has a magnetic field shielding property of 25 dB or more at 100 MHz as measured by the KEC method, more preferably 40 dB or more, even more preferably 60 dB or more, particularly preferably 80 dB or more, and most preferably 90 dB or more. The upper limit of the magnetic field shielding property is not particularly limited, but is, for example, 99 dB or less.
[0037] The electromagnetic wave shielding sheet of the present invention preferably has an electric field shielding property of 60 dB or more, more preferably 70 dB or more, and even more preferably 75 dB or more at 10 MHz as measured by the KEC method. The upper limit of the electric field shielding property is not particularly limited, but is, for example, 99 dB or less.
[0038] Detailed methods for measuring the magnetic shielding property at 100 MHz measured by the KEC method and the electric field shielding property at 10 MHz by the KEC method will be described later. In the present invention, in an extremely thin electromagnetic shielding sheet having a thickness of 900 μm or less, it is preferable that the magnetic field shielding property at 100 MHz measured by the KEC method is 80 dB or more, and the electric field shielding property at 10 MHz is 60 dB or more. In the present invention, by making the electromagnetic shielding sheet have a predetermined layer structure, it has excellent electromagnetic shielding property even when it is extremely thin, having a thickness of 900 μm or less.
[0039] The electromagnetic wave shielding sheet of the present invention is not particularly limited as long as it has a layer structure in which one main surface is a first conductive layer, the other main surface is a second conductive layer, and a magnetic layer is disposed between the first conductive layer and the second conductive layer. For example, the electromagnetic wave shielding sheet may have a conductive layer / magnetic layer / conductive layer, a conductive layer / magnetic layer / conductive layer / magnetic layer / conductive layer, a conductive layer / magnetic layer / conductive layer / magnetic layer / conductive layer, a conductive layer / magnetic layer / conductive layer / magnetic layer / nonwoven fabric layer / conductive layer, a conductive layer / magnetic layer / nonwoven fabric layer / conductive layer / magnetic layer / conductive layer, a conductive layer / magnetic layer / nonwoven fabric layer / conductive layer / magnetic layer / conductive layer, a conductive layer / magnetic layer / binder layer / conductive layer, a conductive layer / magnetic layer / binder layer / conductive layer / magnetic layer / binder layer / conductive layer, Examples of layer configurations include conductive layer / magnetic layer / binder layer / conductive layer / magnetic layer / binder layer / conductive layer / magnetic layer / binder layer / conductive layer, conductive layer / magnetic layer / binder layer / conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer, conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer, conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer / magnetic layer / conductive layer, conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer / magnetic layer / binder layer / nonwoven fabric layer / binder layer / conductive layer, and the like.
[0040] <Manufacturing method of electromagnetic wave shielding sheet> The manufacturing method of the electromagnetic wave shielding sheet is not particularly limited and the sheet can be manufactured by known methods. However, the following describes a manufacturing method in which the conductive layer and the nonwoven fabric layer are commercially available products (finished products), while the magnetic layer is not a commercially available product but is formed using a resin composition for the magnetic layer.
[0041] When a magnetic layer is formed on the surface of a conductive layer, a resin composition for a magnetic layer is applied to the surface of the conductive layer by a method such as coating, vapor deposition, or sputtering, and then dried to obtain a laminate in which the conductive layer / magnetic layer are laminated in this order. In this specification, the "surface" refers to a surface perpendicular to the lamination direction (thickness direction) of the electromagnetic shielding sheet.
[0042] When a nonwoven fabric layer is formed on the surface of a conductive layer, or when another layer is formed on the surface of a magnetic layer or a nonwoven fabric layer, the layers can be laminated via a binder layer. For example, when a nonwoven fabric layer is formed on the surface of a conductive layer, a resin composition for binder layer is applied to the surface of the conductive layer by a method such as coating, and then a nonwoven fabric is attached to the surface of the resin composition for binder layer, followed by drying and thermocompression bonding to obtain a laminate in which the conductive layer / binder layer / nonwoven fabric layer are laminated in this order. The drying and thermocompression bonding may be performed by a known method, for example, at a temperature of 100 to 150° C. and a pressure of 1 to 20 N / cm. 2 This can be done by hot pressing at a pressure of 1000 MPa. EXAMPLES
[0043] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The evaluation methods used in each example and comparative example are as follows.
[0044] (Measurement of unit weight) The basis weight was measured based on "Mass per unit area" in JIS L 1913 (2010) 6.2.
[0045] (Thickness measurement) The thickness of the sample (laminate sheet) was measured based on 6.1 of JIS L 1913 (2010). The thickness of the aluminum foil was measured based on JIS H 4160, and the thicknesses of the magnetic layer and binder layer were measured by cutting the laminate sheet vertically and taking enlarged photographs of the cut surfaces using an electron microscope.
[0046] (Measurement of magnetic field shielding at a frequency of 100 MHz) A sample (laminate sheet) measuring 150 mm in length and 150 mm in width was prepared, and an electromagnetic shielding effectiveness measuring device developed by the Kansai Electronics Industry Development Center (KEC) was used to measure the magnetic field strength M (A / m) in a space where the sample was not present, and the magnetic field strength M' (A / m) when the sample was placed, at a frequency of 100 MHz. The magnetic field shielding performance at a frequency of 100 MHz was then calculated using the following formula. Magnetic field shielding performance (dB) = 20 log 10 (M / M')
[0047] (Measurement of electric field shielding at a frequency of 10 MHz) A sample (laminate sheet) measuring 150 mm in length and 150 mm in width was prepared, and an electromagnetic shielding effectiveness measuring device developed by the Kansai Electronics Industry Development Center (KEC) was used to measure the electric field strength E (V / m) in a space where the sample was not present, and the electric field strength E' (V / m) when the sample was placed, at a frequency of 10 MHz. The electric field shielding performance at a frequency of 10 MHz was then calculated using the following formula. Electric field shielding performance (dB) = 20 log 10 (E / E')
[0048] <Method of manufacturing resin composition for magnetic layer> 100 parts of resin (Byron BX-1001 manufactured by Toyobo Co., Ltd.), magnetic material (Sendust manufactured by Kinseimatic Co., Ltd.), and 250 parts of solvent (150 parts of methyl ethyl ketone, 100 parts of N,N-dimethylformamide) were mixed and heated to 30° C. The amount of magnetic material blended was determined according to the ratio of magnetic material to resin in the magnetic layer. For example, when the basis weight of the magnetic layer was 150 g / m 2 The weight of the resin in the magnetic layer is 50 g / m 2 , the weight of the magnetic material is 100g / m 2When it was desired to achieve the above, 228 parts of the magnetic material was added, which is twice the total amount of the resin and the crosslinking agent described below. Next, the resin was dissolved using a stirrer, and then 14 parts of a crosslinking agent (Tosoh's Coronate HL) was added to the solution to obtain a resin composition for magnetic layers. In Examples 1-3, 1-4, 2-3, and 2-4, ferrite was used instead of sendust as the magnetic material, and the ferrite contained 13 mass% magnetite, 58 mass% manganese ferrite, and 29 mass% zinc ferrite.
[0049] <Method for producing resin composition for binder layer> 100 parts of resin (Vylon BX-1001 manufactured by Toyobo Co., Ltd.) and 200 parts of solvent (methyl ethyl ketone) were mixed and heated to 30°C. Next, the resin was dissolved using a stirrer, and then 14 parts of a crosslinking agent (Coronate HL manufactured by Tosoh Corporation) was added to the solution to obtain a resin composition for binder layers. Note that the binder layers formed in the following examples and comparative examples all had a thickness of 10 μm and a basis weight of 30 g / m. 2 It is.
[0050] <Aluminum foil and polyester nonwoven fabric> Unless otherwise specified, the aluminum foil used in the following examples and comparative examples has a thickness of 20 μm and a basis weight of 28 g / m 2 An aluminum foil manufactured by Toyo Aluminium Co., Ltd. was prepared. The polyester nonwoven fabric used in the following Examples and Comparative Examples had a thickness of 215 μm and a basis weight of 42 g / m. 2 A polyester spunbond nonwoven fabric (model number: 6401N) manufactured by Toyobo Co., Ltd. was prepared. However, in Comparative Example 2-6, the polyester nonwoven fabric had a thickness of 385 μm and a basis weight of 60 g / m 2 The polyester nonwoven fabric used was manufactured by Toyobo Co., Ltd. (model number: 6551N).
[0051] [Example 1-1] A method for producing a laminate sheet in which aluminum foil (conductive layer) A1, magnetic layer C1, binder layer B1, aluminum foil (conductive layer) A2, magnetic layer C2, binder layer B2, and aluminum foil (conductive layer) A3 are laminated in this order will be described below. The above-mentioned resin composition for magnetic layer was applied to the aluminum foil A2 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried for 3 minutes at 150°C using a dryer to obtain a laminate L1 including the aluminum foil A2 and the magnetic layer C2. Next, the above-mentioned resin composition for binder layer was applied to one side of the aluminum foil A3 by a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the laminate L1 on the magnetic layer C2 side was bonded to the surface of the applied resin composition for binder layer, and then dried for 1 minute in a dryer at 120°C, and then dried at 60°C and 10 N / cm 2 The laminate was then heated and pressed under a pressure of 100° C. and then allowed to stand at room temperature for 48 hours to obtain a laminate L2 in which the aluminum foil A2, the magnetic layer C2, the binder layer B2, and the aluminum foil A3 were laminated in this order. Next, the above-mentioned resin composition for the magnetic layer was applied to the aluminum foil A1 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried for 3 minutes at 150°C using a dryer to form a magnetic layer C1 on the surface of the aluminum foil A1. Next, the above-mentioned resin composition for the binder layer was applied to the surface of the magnetic layer C1 by a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the aluminum foil A2 side of the laminate L2 was bonded to the surface of the applied resin composition for the binder layer, and then dried for 1 minute in a dryer at 120°C, and then dried at 60°C and 10 N / cm 2 The magnetic layer C1 was thermocompressed under a pressure of 150 g / m2 and then left at room temperature for 48 hours to obtain a laminated sheet. 2 The basis weight of the sendust, which is the magnetic material in the magnetic layer C1, is 100 g / m 2 The same was true for the magnetic layer C2.
[0052] [Examples 1-2 to 1-4] Except for changing the composition and application amount of the resin composition for the magnetic layer and changing the magnetic material, thickness, and basis weight of the magnetic layers C1 and C2 to those shown in Table 1, a laminate sheet was prepared in the same order as in Example 1-1, in which aluminum foil A1, magnetic layer C1, binder layer B1, aluminum foil A2, magnetic layer C2, binder layer B2, and aluminum foil A3 were laminated.
[0053] [Examples 1-5] The above-mentioned resin composition for magnetic layer was applied to the aluminum foil A1 by a comma coater so as to be 250 g (dry weight) per square meter, and then dried for 3 minutes at 150°C using a dryer to form a magnetic layer C1 on the surface of the aluminum foil A1. Next, the above-mentioned resin composition for binder layer was applied to the surface of the magnetic layer C1 by a comma coater so as to be 30 g (dry weight) per square meter, and the aluminum foil A2 was laminated on the surface of the applied resin composition for binder layer, and then dried for 1 minute in a dryer at 120°C, and then dried at 60°C and 10 N / cm 2 The laminate was then heated and pressed under a pressure of 100° C. and then allowed to stand at room temperature for 48 hours to obtain a laminate sheet in which the aluminum foil A1, the magnetic layer C1, the binder layer B1, and the aluminum foil A2 were laminated in this order.
[0054] [Comparative Example 1-1] A laminate sheet was produced in the same manner as in Example 1-1, except that the binder layer B2 and the aluminum foil A3 were not provided.
[0055] [Comparative Example 1-2] A laminate sheet was produced in the same manner as in Comparative Example 1-1, except that the thickness of the magnetic layers C1 and C2 was changed to 185 μm.
[0056] [Comparative Example 1-3] The above-mentioned resin composition for the magnetic layer was applied to the aluminum foil A1 side of the laminate sheet of Comparative Example 1-1 using a comma coater at 150 g (dry weight) per square meter, and then dried at 150°C for 3 minutes using a dryer to obtain a laminate sheet having a magnetic layer C0 formed on the surface of the aluminum foil A1 side.
[0057] [Comparative Examples 1-4 to 1-6] The above-mentioned resin composition for magnetic layer was applied to aluminum foil A1 using a comma coater, and then dried at 150°C for 3 minutes using a dryer to form a magnetic layer C1 on the surface of the aluminum foil A1, thereby obtaining a laminated sheet. The composition and coating amount of the resin composition for magnetic layer were adjusted so that the thickness and basis weight of the magnetic layer C1 were as shown in Table 1. In Comparative Example 1-5, instead of aluminum foil A1, a 20 μm thick resin composition with a basis weight of 28 g / m was used. 2Two layers of Toyo Aluminium foil are laminated together, with a thickness of 40μm and a basis weight of 58g / m. 2 In Comparative Example 1-6, instead of the aluminum foil A1, a 12 μm thick aluminum foil with a basis weight of 20 g / m was used. 2 The polyester film used was manufactured by Toyobo Co., Ltd.
[0058] [Comparative Example 1-7] The resin composition for binder layer was applied to the surface of aluminum foil A1 using a comma coater so as to be 30 g (dry weight) per square meter, and aluminum foil A2 was laminated to the surface of the applied resin composition for binder layer. Thereafter, the aluminum foil A2 was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 The binder layer resin composition was then applied to the surface of the aluminum foil A2 with a comma coater at 30 g (dry weight) per square meter, and the aluminum foil A3 was laminated to the surface of the applied binder layer resin composition. After that, the aluminum foil A3 was dried for 1 minute in a dryer at 120°C, and then dried at 60°C and 10 N / cm. 2 and then allowed to stand at room temperature for 48 hours to obtain a laminated sheet in which aluminum foil A1, binder layer B1, aluminum foil A2, binder layer B2, and aluminum foil A3 were laminated in this order.
[0059] The layer configurations and physical properties of each layer of the laminate sheets in the examples and comparative examples, as well as the shielding properties of the laminate sheets, are shown in Table 1. In the column for the basis weight of the magnetic layer, the values in parentheses are the basis weight of the magnetic material only, not including the resin.
[0060] [Table 1]
[0061] [Example 2-1] The manufacturing method of a laminated sheet in which aluminum foil (conductive layer) A1, magnetic layer C1, binder layer B1, nonwoven fabric layer N1, binder layer B2, aluminum foil (conductive layer) A2, magnetic layer C2, binder layer B3, nonwoven fabric layer N2, binder layer B4, and aluminum foil (conductive layer) A3 are laminated in this order is described below. The resin composition for the binder layer was applied to the surface of an aluminum foil A3 using a comma coater so as to be 30 g (dry weight) per square meter, and a polyester nonwoven fabric was laminated on the resin composition for the binder layer. After that, it was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 The laminate was then left at room temperature for 48 hours to obtain a laminate L1 in which the nonwoven fabric layer N2, the binder layer B4, and the aluminum foil A3 were laminated in this order. The above-mentioned resin composition for magnetic layer was applied to the surface of the aluminum foil A2 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried at 150° C. for 3 minutes using a dryer to form a magnetic layer C2 on the surface of the aluminum foil A2, thereby obtaining a laminate L2. The magnetic layer C2 had a basis weight of 150 g / m 2 The weight of the magnetic material, Sendust, is 100 g / m 2 It was. The above-mentioned resin composition for binder layer was applied to the surface of the magnetic layer C2 side of the laminate L2 using a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the nonwoven fabric layer N2 side of the laminate L1 was laminated onto the applied resin composition for binder layer. Thereafter, the laminate was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 and then left at room temperature for 48 hours to obtain a laminate L3 having aluminum foil A2, magnetic layer C2, binder layer B3, nonwoven fabric layer N2, binder layer B4, and aluminum foil A3 laminated in this order. The above-mentioned resin composition for magnetic layer was applied to the surface of aluminum foil A1 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried for 3 minutes at 150°C using a dryer to form a magnetic layer C1 on the surface of aluminum foil A1. Next, the above-mentioned resin composition for binder layer was applied to the surface of magnetic layer C1 by a comma coater so as to be 30 g (dry weight) per square meter, a polyester nonwoven fabric was attached to the surface of the applied resin composition for binder layer, and then dried for 1 minute in a dryer at 120°C, followed by drying at 60°C and 10 N / cm 2The laminate was then heated and pressed under a pressure of 100 g / m2 and left at room temperature for 48 hours to obtain a laminate L4 in which the aluminum foil A1, the magnetic layer C1, the binder layer B1, and the nonwoven fabric layer N1 were laminated in this order. The magnetic layer C1 had a basis weight of 150 g / m2. 2 The weight of the magnetic material, Sendust, is 100 g / m 2 It was. The above-mentioned resin composition for binder layer was applied to the surface of the aluminum foil A2 side of the laminate L3 by a comma coater so as to be 30 g (dry weight) per square meter, and then the surface of the nonwoven fabric layer N1 side of the laminate L4 was laminated on the resin composition for binder layer applied to the laminate L3. Finally, it was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2 The laminate was then left at room temperature for 48 hours to obtain a laminate sheet.
[0062] [Examples 2-2 to 2-4, Comparative Example 2-3] Except for changing the magnetic material, thickness, and basis weight of the magnetic layers C1 and C2 to those shown in Table 2, a laminate sheet was prepared in the same order as in Example 2-1, in which aluminum foil A1, magnetic layer C1, binder layer B1, nonwoven fabric layer N1, binder layer B2, aluminum foil A2, magnetic layer C2, binder layer B3, nonwoven fabric layer N2, binder layer B4, and magnetic layer C3 were stacked.
[0063] [Comparative Example 2-1] The above-mentioned resin composition for magnetic layer was applied to one surface of the aluminum foil A1 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried for 3 minutes at 150°C using a dryer to form a magnetic layer C0 on the surface of the aluminum foil A1. Next, the above-mentioned resin composition for binder layer was applied to the other surface of the aluminum foil A1 by a comma coater so as to be 30 g (dry weight) per square meter, a polyester nonwoven fabric was attached to the surface of the applied resin composition for binder layer, and then dried for 1 minute in a dryer at 120°C, followed by drying at 60°C and 10 N / cm 2The laminate was then heat-pressed under a pressure condition of 1000 MPa and left at room temperature for 48 hours to obtain a laminate L1 in which the magnetic layer C0, aluminum foil A1, binder layer B1, and nonwoven fabric layer N1 were laminated in this order. A laminate L2 was also obtained in which the magnetic layer C2, aluminum foil A3, binder layer B5, and nonwoven fabric layer N3 were laminated in this order using the same manufacturing method as for the laminate L1. The above-mentioned resin composition for binder layer was applied to the surface of the nonwoven fabric layer N1 side of the laminate L1 using a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the magnetic layer C2 side of the laminate L2 was bonded to the surface of the applied resin composition for binder layer. Thereafter, the laminate was dried in a dryer at 120°C for 1 minute, and then heated at 60°C and 10 N / cm. 2 The laminate was then heat-pressed under a pressure of 1000 N / cm, and left at room temperature for 48 hours to obtain a laminate L3 in which the magnetic layer C0, aluminum foil A1, binder layer B1, nonwoven fabric layer N1, binder layer B2, magnetic layer C2, aluminum foil A3, binder layer B5, and nonwoven fabric layer N3 were laminated in this order. Finally, the binder layer resin composition was applied to the nonwoven fabric layer N3 side surface of the laminate L3 using a comma coater at 30 g (dry weight) per square meter, and aluminum foil A4 was attached to the surface of the applied binder layer resin composition. After that, the laminate was dried in a dryer at 120°C for 1 minute, and then heated at 60°C and 10 N / cm. 2 The laminate was then heat-pressed under pressure conditions of 1000 to 2000, and left at room temperature for 48 hours to obtain a laminated sheet in which the magnetic layer C0, aluminum foil A1, binder layer B1, nonwoven fabric layer N1, binder layer B2, magnetic layer C2, aluminum foil A3, binder layer B5, nonwoven fabric layer N3, binder layer B6, and aluminum foil A4 were laminated in this order. The thickness and basis weight of the magnetic layer C0 and aluminum foil A4 (layers marked with (*) in Table 2) were the same as those of the magnetic layer C1 and aluminum foil A1, respectively.
[0064] [Comparative Example 2-2] The laminate L3 was produced in the same manner as in Comparative Example 2-1. The above-mentioned resin composition for magnetic body layer was applied to the surface of the nonwoven fabric layer N3 side of the laminate L3 by a comma coater so as to be 150 g (dry weight) per square meter, and then dried at 150 ° C. for 3 minutes using a dryer to obtain a laminate sheet in which the magnetic body layer C0, aluminum foil A1, binder layer B1, nonwoven fabric layer N1, binder layer B2, magnetic body layer C2, aluminum foil A3, binder layer B5, nonwoven fabric layer N3, and magnetic body layer C3 were laminated in this order. The thickness and basis weight of the magnetic body layers C0 and C3 (layers marked with (*) in Table 2) were the same as those of the magnetic body layer C1.
[0065] [Comparative Example 2-4] The laminate L1 was not produced. Instead of the laminate L3, the above-mentioned resin composition for the binder layer was applied to the surface of the magnetic layer C2 side of the laminate L2 using a comma coater so as to be 30 g (dry weight) per square meter. A polyester nonwoven fabric was then laminated on the applied resin composition for the binder layer. After that, the polyester nonwoven fabric was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm. 2 A laminate was prepared in the same manner as in Example 2-1, except that the aluminum foil A1, magnetic layer C1, binder layer B1, nonwoven fabric layer N1, binder layer B2, aluminum foil A2, magnetic layer C2, binder layer B3, and nonwoven fabric layer N2 were laminated in this order by thermocompression bonding under pressure conditions of 1000 V and then left at room temperature for 48 hours to prepare and use a laminate L3' in which the aluminum foil A2, magnetic layer C2, binder layer B3, and nonwoven fabric layer N2 were laminated in this order. A laminate sheet was obtained in which the aluminum foil A1, magnetic layer C1, binder layer B1, nonwoven fabric layer N1, binder layer B2, aluminum foil A2, magnetic layer C2, binder layer B3, and nonwoven fabric layer N2 were laminated in this order.
[0066] [Comparative Example 2-5] A laminate L4 was prepared in the same manner as in Example 2-1, and the above-mentioned resin composition for the magnetic layer was applied to the surface of the nonwoven fabric layer N1 side of the laminate L4 using a comma coater at 160 g (dry weight) per square meter, and then dried at 150°C for 3 minutes using a dryer to form a magnetic layer C2 on the surface of the nonwoven fabric layer N1, thereby obtaining a laminate sheet in which the aluminum foil A1, magnetic layer C1, binder layer B1, nonwoven fabric layer N1, and magnetic layer C2 were laminated in that order.
[0067] [Comparative Example 2-6] The resin composition for binder layer was applied to one surface of the aluminum foil A1 using a comma coater so as to be 30 g (dry weight) per square meter, and a polyester nonwoven fabric was attached to the surface of the applied resin composition for binder layer. Thereafter, the fabric was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm. 2 The laminate was then heat-pressed under a pressure of 10 N / cm and left at room temperature for 48 hours to obtain a laminate in which the aluminum foil A1, the binder layer B1, and the nonwoven fabric layer N1 were laminated in this order. The binder layer resin composition was then applied to the surface of the laminate opposite the aluminum foil A1 using a comma coater at a rate of 30 g (dry weight) per square meter, and a polyester nonwoven fabric or aluminum foil was attached to the surface of the applied binder layer resin composition. The laminate was then dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm. 2 By repeatedly subjecting the laminate to thermocompression bonding under the pressure condition of 100° C. and leaving it at room temperature for 48 hours, a laminate was obtained in which aluminum foil A1, binder layer B1, nonwoven fabric layer N1, binder layer B2, aluminum foil A2, binder layer B3, nonwoven fabric layer N2, binder layer B4, and aluminum foil A3 were laminated in this order.
[0068] [Comparative Example 2-7] The above-mentioned resin composition for magnetic layer was applied to the surface of polyester nonwoven fabric by a comma coater so as to be 180g (dry weight) per square meter, and then dried at 150°C for 3 minutes using a dryer to obtain a laminate L1 of magnetic layer C1 and nonwoven fabric layer N1. Next, the above-mentioned resin composition for magnetic layer was applied to the surface of polyester nonwoven fabric other than the above-mentioned polyester nonwoven fabric by a comma coater so as to be 180g (dry weight) per square meter, and then dried at 150°C for 3 minutes using a dryer to obtain a laminate L2 of magnetic layer C2 and nonwoven fabric layer N2. Finally, the above-mentioned resin composition for binder layer was applied to the surface of the nonwoven fabric layer N1 side of the laminate L1 using a comma coater so as to be 30 g (dry weight) per square meter, and the surface of the magnetic layer C2 side of the laminate L2 was bonded to the surface of the applied resin composition for binder layer. Thereafter, the laminate was dried in a dryer at 120°C for 1 minute, and then dried at 60°C and 10 N / cm 2and then allowed to stand at room temperature for 48 hours to obtain a laminated sheet in which the magnetic layer C1, nonwoven fabric layer N1, binder layer B2, magnetic layer C2, and nonwoven fabric layer N2 were laminated in this order.
[0069] [Comparative Example 2-8] A laminate L1 was prepared in the same manner as in Example 2-1, and the above-mentioned resin composition for the magnetic layer was applied to the surface of the nonwoven fabric layer N2 side of the laminate L1 using a comma coater at 595 g (dry weight) per square meter, and then dried at 150°C for 3 minutes using a dryer to form a magnetic layer C2 on the surface of the aluminum foil A2, thereby obtaining a laminate sheet.
[0070] [Comparative Example 2-9] A laminate L4 was prepared in the same manner as in Example 2-1, except that the magnetic material, thickness, and basis weight of the magnetic layers C1 and C2 were changed to those shown in Table 2, and two sheets of the above polyester nonwoven fabric were stacked to form the nonwoven fabric layer N1, to form a laminate sheet.
[0071] The layer configurations and physical properties of each layer of the laminate sheets in the examples and comparative examples, as well as the shielding properties of the laminate sheets, are shown in Table 2. In the column for the basis weight of the magnetic layer, the values in parentheses are the basis weight of only the magnetic material, excluding the resin.
[0072] [Table 2]
[0073] In Examples 1-1 to 1-5 and 2-1 to 2-4, the laminated sheets have a predetermined layer structure, and therefore are excellent in electromagnetic wave shielding properties.
Claims
1. An electromagnetic wave shielding sheet including a first conductive layer, a second conductive layer, and a magnetic layer, one main surface of the electromagnetic wave shielding sheet is the first conductive layer, the other main surface is the second conductive layer, and the magnetic layer is disposed between the first conductive layer and the second conductive layer; The electromagnetic wave shielding sheet, wherein the first conductive layer and the second conductive layer each contain a conductive material, and the magnetic layer contains a magnetic material.
2. 2. The electromagnetic shielding sheet according to claim 1, wherein the conductive material comprises at least one material selected from the group consisting of conductive polymers, metals, metal oxides, and carbon-based materials.
3. 2. The electromagnetic shielding sheet according to claim 1, wherein the magnetic material is a soft magnetic material.
4. 2. The electromagnetic shielding sheet according to claim 1, further comprising a nonwoven fabric layer as an intermediate layer.
5. The electromagnetic shielding sheet according to claim 4 , wherein the nonwoven fabric layer contains a polyester resin.
6. 6. The electromagnetic wave shielding sheet according to claim 1, having a thickness of 900 μm or less, a magnetic field shielding property at 100 MHz measured by the KEC method of 80 dB or more, and an electric field shielding property at 10 MHz of 60 dB or more.
Citation Information
Patent Citations
Inflammable electromagnetic wave shield laminate and inflammable electromagnetic wave shielding wall material produced using the same
JP2019179786A
Multilayer electromagnetic shielding composite
JP2022075645A